SYN-RIFT SANDSTONЕS: THE FEATURES OF BULK CHEMICAL COMPOSITIONS, AND POSITIONS ON PALEOGEODYNAMIC DISCRIMINANT DIAGRAMS - A. V. Maslov; V. N. Podkovyrov; E. Z. Gareev; N. D. Sergeeva (Геодинамика и тектонофизика)
From the early 1980s, the data on the bulk chemical composition of sandstones and mudstones are actively involved for interpretation of the paleogeodynamic settings for sedimentary sequences. Discriminant diagrams such as K2O/Na2O–SiO2/Al2O3 [Maynard et al., 1982], (Fe2O3*+MgO)–K2O/Na2O and others [Bhatia, 1983], SiO2–K2O/Na2O [Roser, Korsch, 1986], (K2O+Na2O)–SiO2/20–(TiO2+Fe2O3+MgO) [Kroonenberg, 1994] etc., are now widely used in regional investigations to classify terrigenous rocks from several paleogeodynamic settings (passive and active continental margins, oceanic and continental volcanic arcs etc.) with a certain ‘percentage of consistency’. The first diagrams DF1–DF2 for syn-rift compositions were published in the early 2010s [Verma, Armstrong-Altrin, 2013]. This article analyzes the bulk chemical compositions of syn-rift sandstones from intracratonic rifts and rifts formed during the break-up of the Columbia and Gondwana supercontinents, rifts within volcanic arcs and related to the collapse of collision orogens (for example, Permian sandstones of the Malužiná formation, Western Carpathians, Slovakia). Our database includes the Neoproterozoic Uinta Mountain Group (USA), the Cretaceous Omdurman formation of the Khartoum Basin (Sudan), the siliciclastic deposits of the Kalahari Basin (East African rift zone), the sandstones of the Vindhyan Supergroup (India), the Neoproterozoic Ui Group of the Uchur-Maya region (Southeast Siberia), the Meso-Neoproterozoic Banxi Group (Southern China), the Mesoproterozoic Belt-Purcell Supergroup (USA), the Oronto and Bayfield Groups of the Midcontinent (USA), as well as the sandstones of the Upper Precambrian Ai and Mashak formations, and the metasedimentary rocks of the Arsha Group (Southern Urals). The article examines: (1) the position of the syn-rift sandstone compositions (fields) on the log(SiO2/Al2O3)–log(Na2O/K2O) classification diagram and the F1–F2 diagram, which gives the possible composition of the catchment areas rocks; (2) the position of the syn-rift sandstone compositions, as well as the average values of various indicator ratios and discriminant functions, in the K2O/Na2O–SiO2/Al2O3, F3–F4, SiO2–K2O/Na2O and DF1–DF2 diagrams. The analysis of the results shows that the fields of the syn-rift sandstones are characterized by a wide dispersion of log(SiO2/Al2O3) (0.4…3.5) and log(Na2O/K2O) values (~0.2…6.0 and more). A number of the values do not fit into the typical areas on the classification diagram of F.J. Pettijohn et al., which suggests that the syn-rift sandstones vary considerably in composition that is controlled by a significant number of factors. The diagram of J. Maynard et al. is not suitable for assigning certain sandstone associations to the ‘syn-rift sandstones’ category. In the diagrams of M. Bhatia and K. Crook, as well as those of B. Roser and R. Korsch, the fields and mean points of the syn-rift sandstones are mainly located in the area of passive continental margins; thus, these diagrams can not be used to classify the syn-rift sandstone associations. Contrariwise, on the high-silica DF1–DF2 diagram [Verma, Armstrong-Altrin, 2013], ~80 % of the objects from our database are localized in the field of syn-rift compositions and show a good correlation with the ‘percentage of consistency’ evaluated by the authors for the samples from similar settings (79–85 %). Thus, according to the data presented in the article, the DF1–DF2 diagram is the most rational and acceptable discriminant diagram for assigning certain sandstone associations to the ‘syn-rift infilling’ category.